Calculation of the ALMA Risk of Right Ventricular Failure After Left Ventricular Assist Device Implantation. Issue 6 (November 2018) - Loforte, Antonio; Montalto, Andrea; Musumeci, Francesco; Amarelli, Cristiano; Mariani, Carlo; Polizzi, Vincenzo; Lilla Della Monica, Paola; Grigioni, Francesco; Di Bartolomeo, Roberto; Marinelli, Giuseppe
Abstract : Right ventricular failure after continuous-flow left ventricular assist device (LVAD) implantation is still an unsolved issue and remains a life-threatening event for patients. We undertook this study to determine predictors of the patients who are candidates for isolated LVAD therapy as opposed to biventricular support (BVAD). We reviewed demographic, echocardiographic, hemodynamic, and laboratory variables for 258 patients who underwent both isolated LVAD implantation and unplanned BVAD because of early right ventricular failure after LVAD insertion, between 2006 and 2017 (LVAD = 170 and BVAD = 88). The final study patients were randomly divided into derivation (79.8%, n = 206) and validation (20.1%, n = 52) cohorts. Fifty-seven preoperative risk factors were compared between patients who were successfully managed with an LVAD and those who required a BVAD. Nineteen variables demonstrated statistical significance on univariable analysis. Multivariable logistic regression analysis identified destination therapy (odds ratio [OR] 2.0 [1.7–3.9], p = 0.003), a pulmonary artery pulsatility index <2 (OR 3.3 [1.7–6.1], p = 0.001), a right ventricle/left ventricle end-diastolic diameter ratio >0.75 (OR 2.7 [1.5–5.5], p = 0.001), an right ventricle stroke work index <300 mm Hg/ml/m 2 (OR 4.3 [2.5–7.3], p < 0.001), and a United Network for Organ Sharing modified Model for End-Stage Liver Disease Excluding INR score >17 (OR 3.5 [1.9–6.9], p < 0.001) as the major predictors of the need for BVAD. Using these data, we propose a simple risk calculator to determine the suitability of patients for isolated LVAD support in the era of continuous-flow mechanical circulatory support devices.